Zad.1
Rozwiąż równania

a) 6x = 3
b) -3x = 7
c) 2x = 1/5
d) 1,2x = 4,8
e) 1/3x = 3
f) -3/5x = -5
g) 3/4x = -4/9
h) 0,1x = -7

Zad.2
Rozwiąż równania

a) 10x + 4 = 7
b) 4x - 3 = 9
c) -2x + 2 = -7
d) 6x + 5 = 4x
e) 9x - 3 = 2x + 5
f) -3x + 4 = -5x - 1

Zad. 3
Rozwiąż równania

a) 0,1x + 0,2 = -0,3
b) 0,25x + 0,4 = 0,35
c) 1 - 0,2x = -0,3x
d) 0,01x - 1 = 0,1x - 0,1


Odpowiedź :

Odpowiedź:

Zad.1

Rozwiąż równania

a)

6x = 3     /:6

x = 3/6 = 1/2

b)

-3x = 7     /:(-3)

x = -7/3 = -2 1/3

c)

2x = 1/5      /:2

x = 1/5 * 1/2 = 1/10

d)

1,2x = 4,8      /:1,2

x = 4

e)

1/3x = 3     /*3

x = 9

f)

-3/5x = -5      /*(-5/3)

x = 5 * 5/3 = 25/3 = 8 1/3

g)

3/4x = -4/9       /*4/3

x = -4/9 * 4/3 = -16/27

h)

0,1x = -7    /:0,1

x = -70

Zad.2

Rozwiąż równania

a)

10x + 4 = 7

10x = 7 - 4        /:10

x = 3/10

b)

4x - 3 = 9

4x = 9 + 3      /:4

x = 12/4 = 3

c)

-2x + 2 = -7

-2x = -7 - 2     /:(-2)

x = 9/2 = 4 1/2

d)

6x + 5 = 4x

6x - 4x = -5

2x = -5     /:2

x = -5/2 = -2 1/2

e)

9x - 3 = 2x + 5

9x - 2x = 5 + 3

7x = 8      /:7

x = 8/7 = 1 1/7

f)

-3x + 4 = -5x - 1

-3x + 5x = -1 - 4

2x = -5     /:2

x = -5/2 = -2 1/2

Zad. 3

Rozwiąż równania

a)

0,1x + 0,2 = -0,3

0,1x = -0,3 - 0,2     /:0,1

x = -0,5/0,1 = -5

b)

0,25x + 0,4 = 0,35

0,25x = 0,35 - 0,4    /:0,25

x = -0,05 : 0,25 = 0,2

c)

1 - 0,2x = -0,3x

-0,2x + 0,3x = -1

0,1x = -1       /:0,1

x = -10

d)

0,01x - 1 = 0,1x - 0,1

0,01x - 0,1x = -0,1 + 1

-0,09x = 0,9       /:(-0,09)

x = -10

Szczegółowe wyjaśnienie: